2018
DOI: 10.1038/s41533-018-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study of LAMA monotherapy effectiveness compared with LABA/LAMA as initial treatment for COPD in primary care

Abstract: This epidemiological study aimed to describe and compare the characteristics and outcomes of COPD patients starting treatment with a long-acting anti-muscarinic (LAMA) or a combination of a long-acting beta-2 agonist (LABA)/LAMA in primary care in Catalonia (Spain) over a one-year period. Data were obtained from the Information System for the Development in Research in Primary Care (SIDIAP), a population database containing information of 5.8 million inhabitants (80% of the population of Catalonia). Patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…These results coincide with Castelino et al [27] who reported majority of your study were males (90.7%). Similarly, Barrecheguren and colleagues [28] stated that 76.9% of the sample was male. These result inconsistent with Raghavan et al [29] who conducted study "chronic obstructive pulmonary disease: the impact of gender", they found that women are higher prevalence as compared with male.…”
Section: Discussionmentioning
confidence: 91%
“…These results coincide with Castelino et al [27] who reported majority of your study were males (90.7%). Similarly, Barrecheguren and colleagues [28] stated that 76.9% of the sample was male. These result inconsistent with Raghavan et al [29] who conducted study "chronic obstructive pulmonary disease: the impact of gender", they found that women are higher prevalence as compared with male.…”
Section: Discussionmentioning
confidence: 91%
“…P days supplied study period (this method is sometimes called the medication refill adherence) [57, 84, 89, 120, 131-133, 148, 165, 166, 174, 180, 183] (4) P days supplied study period À inpatient days [80] (5) P days supplied À inpatient days study period À inpatient days [80] mMPR: in this case, the denominator of the MPR is modified from days between first and last prescription to days between first and last dispensing+duration of last prescription (6) P days supplied days between first and last dispensing þ duration of last prescription in days [29,46,82,[94][95][96][97] (7) ( P days supplied of each inhaler device )=number of inhalers duration of therapy [179] Unclear MPR calculation [87,113,142,143,164,175] PDC: the proportion of days covered is the ratio of the sum of the days covered by a medication (numerator) to a fixed time period (denominator, e.g. 365 days) [4,11] or to the study period [4,13] Denominator: fixed time period ( 8) study period [116][117][118] Other definitions of PDC (14) The relationship between the proportion of the billed doses of pharmacy and the number of days covered according to the labelling of the product [33,90] (15) Quantity dispensed (unclear whether in days or canisters) fixed time period [153] No definition available [58,164,169] Unclear definition [34] A combination of PDC and MPR: the numerator is a variant of the days supplied or the days covered and/or the denominator is a fixed time period or a variant of the study period…”
Section: Adherence Measurement Methodsmentioning
confidence: 99%
“…Bogart et al 36 performed an adherence calculation, for which 365 days were defined as the study period. Similarly, Cyr et al 37 and Barrecheguren et al 38 used the same interval for computing PDC. The results of the studies in which a 365-day period is used for the PDC calculation confirm that patients with COPD have low adherence to drug therapy.…”
Section: Prasungriyo N and Sooksai N Counseling And Readmissions In Aecopd Patientsmentioning
confidence: 99%